Analisis Aktivitas Penghimpunan dan Penyaluran Dana Berdasarkan Konsep Mudharabah di Bank Nagari Syariah Solok - Ihsan, Diky Nafisa; Martilova, Novera; Dewi, Sandra (Lembaga Yasin AlSys, 2024)
This research aims to analyze fund raising and distribution activities based on the Mudharabah concept at Bank Nagari Syariah Solok. Bank Nagari Syariah is a financial institution based on Islamic Sharia principles which aims to improve community welfare through improving economic business performance. This research uses a qualitative descriptive approach by collecting data through interviews and documents from Bank Nagari Syariah. The results of this research show that the number of customers collecting funds through savings, deposits and current accounts continues to increase in the 2019-2023 period. This reflects the high level of public trust in Bank Nagar Syariah Solok. In addition, the increase in the number of customers who share money through mudharabah products for both investment and working capital shows the important role of Bank Nagari Syariah in supporting the real sector and micro, small and medium enterprises. (UMKM) Based on the results of the research conducted, it can be concluded that the mudharabah concept implemented at Bank Nagar Syariah Solok is effective in collecting and distributing funds and has great potential in consistently improving the community's economy. . with sharia principles, but the biggest challenge is a lack of understanding. to the public about sharia products that require additional education from the bank.